Sex-related variation in compact bone microstructure of the femoral diaphysis in juvenile rabbits - Martiniaková, Monika (BioMed Central, 2008)
BACKGROUND: While gross morphological changes in the skeleton between males and females are well know, differences between sexes in the histomorphology are less known. It is important to have knowledge on the bone structure of rabbits, as this is a widely used species in biomedical research. A study was performed to evaluate the association between sex and the compact bone morphology of the femoral diaphysis in juvenile rabbits. METHODS: Seventeen clinically healthy 2–3 month-old rabbits (9 females, 8 males) were included in the study. The rabbits were euthanized and the right femur was sampled for analysis. 70–80 microns thick bone sections of the femoral diaphysis were prepared using standard histological equipment. The qualitative histological characteristics were determined according to internationally accepted classification systems while the quantitative parameters were assessed using the software Scion Image. Areas, perimeters, minimum and maximum diameters of primary osteons' vascular canals, Haversian canals and secondary osteons were measured. Additionally, blood plasma concentrations of progesterone, corticosterone, IGF-I, testosterone and estradiol were analyzed. RESULTS: Qualitative histological characteristics were similar for both sexes. However, variations of certain quantitative histological characteristics were identified. Measured parameters of the primary osteons' vascular canals were higher in males than for females. On the other hand, females had significant higher values of secondary osteons parameters. Differences in Haversian canals parameters were only significant for minimum diameter. CONCLUSION: The study demonstrated that quantitative histological characteristics of compact bone tissue of the femoral diaphysis in juvenile rabbits were sex dependent. The variations may be associated with different growth and modeling of the femur through influence by sex-specific steroids, mechanical loads, genetic factors and a multitude of other sources. The results can be applied in experimental studies focusing on comparison of the skeletal biology of the sexes.